Self-confidence attitude of novice primary teachers reflection on teaching mathematics - Enditiyas Pratiwi; A.Wilda Indra Nanna; Dedi Kusnadi; Irianto Aras; Dian Kurniati; Percy Sepeng (Jurnal Elemen, 2022)
The teacher’s attitude towards mathematics teaching is seen as an essential factor in forming students’ attitudes towards mathematics. However, no one has extensively described the reflection of teachers’ self-confidence in teaching mathematics, especially for novice primary teachers. Therefore, the purpose of this study sought to describe a reflection of the self-confidence attitude of novice primary teachers in teaching mathematics. A questionnaire based on novice primary teachers’ teaching experience was administered to a total of 28 novice primary teachers (N = 22 males, N = 6 females) conveniently selected to participate in the study reported in this article. The semi-structured interviews data explored novice primary teachers’ reflections on the given questionnaire scale items. The qualitative data obtained from semi-structured interviews informed the quantitative information extracted from the questionnaires. The results showed that the reflection of the self-confidence attitude of novice primary teachers in low, moderate, and high participants on the scale of confidence in teaching mathematics raises three essential findings, specifically (1) ability on content knowledge, (2) ability to explain, and (3) ability in classroom management. The resulting reflection in low, moderate, and high participants on the scale was an attitude toward success in teaching mathematics, namely, the appraisal of others, and on the scale, the usefulness of mathematics teaching, namely the ability to understand the usefulness of mathematics.